Case Case Study Of Combination Of Progressive Muscle Relaxation (PMR) And Guided Imagery In Ovarial Cancer Patients - Trisna Lavenia; Desy Ayu Wardani; Yanti Zachrailly (Jurnal Keperawatan Malang, 2022)
Background: Cancer is a major public health problem worldwide, thousands of new cases of ovarian cancer are diagnosed every year with a high mortality rate globally. Anxiety and pain, both acute and chronic, are complications that are almost certainly experienced by patients with ovarian cancer. The cause of ovarian cancer is still unclear, but several factors that may be associated with the onset of this disease include reproductive factors, menstrual factors, environmental factors, and genetic factors (Kampono N, et al, 2011). Objective: This study aims to determine the Anxiety Score and Acute and Chronic Pain Score in ovarian cancer patients before and after the Combination of Progressive Muscle Relaxation (PMR) and Guided Imager. Methods: This study uses a case study design and the application of Evidence Based Nursing Combination of Progressive Muscle Relaxation (PMR) and Guided Imagery. The sampling technique was Accidental Sampling with a sample of 3 respondents in the intervention group using the Visual Analog Scale for Anxiety and the Numeric Rating Scale (NRS). Results: Anxiety scores on the first day were on a scale of 5.4, and 8, then on the second day it became 3, and 7. Then the Pain score on the first day was 4, 6, and 8 then on the second day it became 3, and 7. Conclusion: The results of the study showed a change in the Anxiety Score and Pain Score before and after the combination of Progressive Muscle Relaxation (PMR) and Guided Imagery. The application of this combination can be used to help reduce anxiety and pain in Ovarian Cancer patients.